Human agent support model for volunteers during flood - Alwi, Asmidah; Ab. Aziz, Azizi; Che Pa, Noraziah; Abu Bakar, Juliana Aida; Mohd Shabli, Ahmad Hanis; Wan Ismail, Wan Mohd Taufik (2016)
Stress is a common psychological stimulus that occurs in a person caused by stressors.Natural disaster is a specific form of stressor that can carry wide area of implications in the population. It is the most common factors which contribute to high level of stress and other psychological problems of individuals.This paper presents a dynamic of a human agent-based model for volunteer’s stress.The aim of this project is to determine the level of occupational stress among the volunteers and to evaluate the proposed model via simulation results.Based on several individual features, environmental situation, and both forms presentation of events (i.e. psychological and physiological stressors), the agent model can simulate whether a human agent combining ambient agent that experience certain scenarios will face into a stress condition.A number of well-known relations between events and the course of stress are summarized and it is shown that the model exhibits their patterns.From the developed models, a variety of simulation experiments was conducted.In addition, the agent model has been evaluated using Temporal Trace Language to confirm the results.